2021
DOI: 10.3389/fimmu.2020.608895
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Induced Microbiome Adaptations Associate With Increased BCAA Levels and Enhance Severity of Influenza Infection

Abstract: Involvement of gut microbiota in pulmonary disease by the gut-lung axis has been widely observed. However, the cross-talk messengers between respiratory mucosal immunity and gut microbiota are largely unknown. Using selective pharmacologic destruction of gut microenvironment mouse models, we found gut microbiota displayed significantly lower alpha diversity and relative abundance of bacteria in Gentamicin treated mice. Metagenomic studies revealed functional differences in gut bacteria in altering metabolic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Furthermore, GNT activated Tregs to reduce the mortality of LPS-induced mice, and decreased the concentrations of pro-inflammatory cytokines and increased the concentrations of anti-inflammatory cytokines, contributing to the recovery of neonatal sepsis. Additionally, Sun et al showed that the pre-treatment of mice with GNT regulates the microbiota into guts and could impair the immune response to influenza virus infection [ 33 ]. However, whether the beneficial effects of GNT in sepsis were related to the reduction of bacterial translocation from guts and/or sepsis-related infection need further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, GNT activated Tregs to reduce the mortality of LPS-induced mice, and decreased the concentrations of pro-inflammatory cytokines and increased the concentrations of anti-inflammatory cytokines, contributing to the recovery of neonatal sepsis. Additionally, Sun et al showed that the pre-treatment of mice with GNT regulates the microbiota into guts and could impair the immune response to influenza virus infection [ 33 ]. However, whether the beneficial effects of GNT in sepsis were related to the reduction of bacterial translocation from guts and/or sepsis-related infection need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Tregs in sepsis remains controversial. Hotchkiss et al reported that Tregs impair immunity and contribute to contribute to nosocomial infections and mortality [33]. However, several studies have shown that activated Tregs prevent polymicrobial sepsis mortality [32,34], and regulate the activation status and antigen-presenting cell function and produce anti-inflammatory cytokines, which are beneficial to sepsis [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota metabolites are considered important mediators of gut-lung interactions. For example, gentamicin induced disorder of gut microbiota results in increased branched-chain amino acids levels that suppress immune cells development which could contribute to enhanced severity of the influenza infection ( 28 ). In addition, gut microbiota dysbiosis aggravated lung histopathologic injury, up-regulated pro-inflammatory cytokine production and air-blood permeability, and increased bacterial load caused by avian pathogenic Escherichia coli , which partially due to reduced gut microbiota-derived acetate levels ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al described the effect of the gentamicin intervention in mice infected with the Influenza virus. Besides the reduced survival of the mice, gentamicin treatment also resulted in an increased abundance of Bacteroidetes, decreased abundance of Proteobacteria, and elevated serum BCAA concentration [79].…”
Section: The Effect Of Microbiota Modulation With Phytochemicals or Symbiotics On The Bcaa Metabolismmentioning
confidence: 99%
“…The functional capacity of the gut microbiota was derived from its composition using PICRUSt [74,77], predicted by pathway analysis based on metabolome composition [48] or using both approaches [75,78]. Currently, there is only one available human study describing the effect of symbiotic (SG) administration (Bifidobacterium lactis UBBLa-70 + fructooligosaccharide) in combination with low-energy intervention in obese women [79]. Both interventions led to a comparable weight loss but the serum BCAA concentration decreased only in the SG-supplemented group.…”
Section: The Effect Of Microbiota Modulation With Phytochemicals or Symbiotics On The Bcaa Metabolismmentioning
confidence: 99%